An assessment of the coastal erosion at Marathon, East Attica (Greece). - Dimou, A.; Vassilakis, E; Antoniou, V.; Evelpidou, N. (10th International Congress of the Hellenic Geographical Society, 22-24 October, 2014)
The 7 kilometers long coastline of Marathon Gulf (East Attica, Greece), has been chosen for this study, in order to classify its coastal erosion, using the Coastal Vulnerability Index (CVI) through GIS technology, since several incidents of erosion have been identified during the past decades in the area. The CVI index is used for assessing the vulnerability of a coast to an anticipated future sea-level rise. It relates geological (coastal geomorphology, historical changes of coastline’s position, coastal slopes) and oceanographic (wave height, run up and tidal range) variables in a semi-quantitative manner. We combined different kinds of datasets extracted from high resolution panchromatic aerial photographs of several time periods (1960-2010) and traced the contemporary shoreline by high accuracy surveying with Real Time Kinematic (RTK) GPS equipment. The interpretation of all shorelines required geo-statistical analysis in a Geographical Information System, in order to estimate the rate of shoreline change for a period of 53 years. Retreating rates were calculated for each section reaching the value of 0.6 m/yr. According to the produced CVI values (10.61- 39.52), it is found that 46% of the coast has very high vulnerability, 20% high vulnerability, whilst 29% have low vulnerability. The area named “Plesti” at the southern part of the study area, a large segment at the coast of Nea Makri, the northern part of Agios Panteleimonas beach and the eastern estuary of the Inois river are those with the higher risk. These conclusions are in full agreement with the field observations.